Influence of perimeter layers on tension mechanical properties of 3D printed Onyx - Coca-Gonzalez, Manuel; Torres-Cedillo, Sergio G.; Alfaro-Ponce, Mariel; Cortés Pérez, Jacinto; Díaz-Montiel, Paulina; Jimenez-Martinez, Moises (Frontiers in Mechanical Engineering, 2025)
Additive Manufacturing has become a vital component of the global economy, revolutionizing manufacturing processes, enhancing mechanical components, and addressing current industry challenges such as increasing production rates. This study explores the tensile strength and stiffness of 3D-printed Onyx, focusing on the effects of printed perimeter layers. Results show that increasing perimeter layers enhances tensile strength by thickening external walls and improving stress distribution. Experiments demonstrate improvements between 2 and 15 layers do not exceed 20%, and perimeter layers show no impact on toughness. Also, internal infill patterns and density play a more significant role in overall strength once sufficient perimeter layers are in place. Two layers are typically sufficient to ensure cohesion, minimize deformation, and prevent micro-crack propagation. Onyx’s nylon matrix and carbon fibers further improve durability by mitigating stress concentrations in the transition zone between the perimeter and inner layers. However, beyond a certain point, additional layers yield diminishing returns, primarily increasing material consumption without significant strength gains. These findings support future research into additional properties like shear strength and impact resistance while balancing performance, material use, and sustainability.